2013
DOI: 10.1093/nar/gkt593
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent bending rigidity and helical twist of DNA by rearrangement of bound HU protein

Abstract: HU is a protein that plays a role in various bacterial processes including compaction, transcription and replication of the genome. Here, we use atomic force microscopy to study the effect of HU on the stiffness and supercoiling of double-stranded DNA. First, we measured the persistence length, height profile, contour length and bending angle distribution of the DNA–HU complex after different incubation times of HU with linear DNA. We found that the persistence and contour length depend on the incubation time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
(39 reference statements)
0
19
1
Order By: Relevance
“…12. The time-dependent bending rigidity observed in a recent experiment 10 might be explained by the fact that (a) the initial formation of rigid HU¯laments, (b) the spiral rearrangement of the proteins and (c) the supercoiling of the double strand might take place at completely di®erent time scales.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…12. The time-dependent bending rigidity observed in a recent experiment 10 might be explained by the fact that (a) the initial formation of rigid HU¯laments, (b) the spiral rearrangement of the proteins and (c) the supercoiling of the double strand might take place at completely di®erent time scales.…”
Section: Discussionmentioning
confidence: 88%
“…9 Recent experimental observation revealed that, even at moderate salt concentrations, the bimodal behavior does not survive for long time scales (&2 h) due to the ability of the HU proteins to rearrange around the DNA. 10 Interestingly, HU¯laments tend to form spiral con¯gurations that excite supercoiling, which could potentially promote DNA compaction and regulate the promoter activity. 6,8,11,12 Atomistic simulation is the most accurate method to study protein-DNA complexes.…”
Section: Introductionmentioning
confidence: 99%
“…HU (histone-like protein from Escherichia coli strain U93) is a small and abundant chromosomal architectural protein 25 that plays important roles in gene regulation, DNA replication, recombination and repair 26 27 . Previous studies on HU using magnetic tweezers 19 20 and atomic force microscopy imaging 20 28 showed that HU bends DNA at low protein concentrations but forms a nucleoprotein filament at higher protein concentrations (≥600 nM) that extends DNA. This bimodal binding behaviour is sensitive to salt concentration 29 and has been observed in single-molecule studies with the B. subtilis homologue HBsu 18 .…”
Section: Resultsmentioning
confidence: 99%
“…To explain the seemingly disparate observations of the transitory dynamics of HU with its critical importance to nucleoid organization, we propose a model in which HU, through the collective sum of a large number of weak, transitory interactions with chromosomal DNAs, maintains the viscoelastic properties and fluidity of the bacterial nucleoid (Figure 5). We use these lines of evidence to support our hypothesis: (1) nucleoids of E. coli can undergo global changes in morphology in as little as 5s 57 , which presumably necessitates dynamic, transiently bound NAPs and increased DNA flexibility; (2) loss of HU disrupts small DNA loop formation in vivo 27 , very likely due to an increase in DNA persistence length as demonstrated by in vitro single molecule experiments 23, 58 ; (3) HU does not play a static architectural role in chromosome organization, as significant modulation of nucleoid condensation through drug treatments did not significantly alter HU dynamics or localization (Figure 3 and S11), unlike the loss of chromosomal dsDNA binding in the triKA mutant (Figure 2); and (4) in the event of HU deletion, our theory predicts a global change in the mechanical properties of the DNA, consistent with the previously observed changes in DNA replication 10 , recombination 17, 59 , gene expression 12 , and nucleoid segregation 60 in a HU deletion background. The viscoelastic maintenance model has been demonstrated for other systems-for example, the non-specific, transitory interactions of the muscle protein α-actinin modulates the mechanical properties of the actin filament network to form a viscoelastic gel 61 .…”
Section: Discussionmentioning
confidence: 59%